Loss of Renal Allografts Secondary to Candida Vascular Complications in Two Recipients from the Same Donor - Govardhana Rao Yannam; Lucile Wrenshall; R. Brian Stevens (Case Reports in Transplantation)
Infections remain a major cause of morbidity and mortality in transplant patients. Organ recipients are also susceptible to donor-derived pathogens and the majority of donor infections are easily treatable. Rarely, some pathogens have produced life-threatening complications by compromising the vascular anastomosis. In this case series we report loss of two kidney allografts secondary to vascular complications due to Candida albicans. Both recipients received grafts from a common donor, in whom Candida bacteremia in the donor was not apparent at the time of organ acceptance but became apparent on delayed cultures.